Upaya Perlawanan sebagai Akibat Pernyataan Dismissal oleh Ketua Pengadilan Tata Usaha Negara (Studi Kasus di Pengadilan Tata Usaha Negara Denpasar) - Anak Agung Tias Sandya Dianti; Anak Agung Sagung Laksmi Dewi; I Nyoman Sugiarta (Warmadewa Press, 2020)
The State Administrative Court (PTUN) is held to resolve conflicts of interest that cause disputes between State Administrative Bodies or Officials and citizens. The object of the dispute becoming the authority of PTUN is a written stipulation issued by a State Administration Agency or Official which causes legal consequences and harm to a person or legal entity in a civil manner which is included in the definition of a State Administrative Decree and contained in Article 2 of Law No.5 1986. This study focuses on the resolution of resistance efforts as a result of dismissal statements by the Chairman of the State Administrative Court and the basis for consideration of the Panel of Judges in deciding the case. To achieve this goal, exploration with this research is carried out using a qualitative research design. The results show that the PTUN Law which is used as a reference in stating a lawsuit can be processed or not through the screening stage, which will then be examined and decided by the appropriate Judge, appointed by the Chief Justice with a short procedure. If the plaintiff’s resistance is accepted, the dismissal determination does not pass by the head of the court is canceled. Furthermore, the subject of the lawsuit will be examined and decided according to an ordinary procedure, and vice versa, if the verzet is rejected by the panel of judges examining it, the plaintiff can no longer take legal action. In deciding cases of resistance action as a result of dismissal, it is stated that the decision on the object of the dispute is included in the category of decisions that are exempt from being a State Administrative Decree.